MULTILITERACIES AND PRODUCTION OF IDENTITY IN CONTEMPORARY SOCIETY: ANALYZING STATEMENTS MULTIMODAL - Dulce Marcia Cruz; Lidnei Ventura; Thais Ehrhardt de Souza (Editora da Universidade de Santa Cruz do Sul, 2015)
This paper investigates the possible relations of determination between multiliteracies and identity production in contemporary times. It starts from the principle that the identities, as they occur in late modernity, are constantly changing and they are formed and continuously transformed. Under these conditions, the self-referencing processes are marked by narratives from "me" influenced by abstract systems, among which stands out the digital media. The central argument of this paper is that multimedia authoring conditions allowed by current digital media, generating various discursive genres, while producing identities, are expressions of them, both in the culture and technologies used. Methodologically, to exemplify how digital media may allow manifestations of lifestyles and identities, it proceeds to the analysis of a You Tube Video from the interpretive scheme of Rojo (2013) takes such multimedia production as a statement multi semiotic and multimodal, proceeds to the analysis of a YouTube video that depicts a compilation album of Adoniran Barbosa.